2005
DOI: 10.1002/cbm.42
|View full text |Cite
|
Sign up to set email alerts
|

Animal abuse among preadolescents directly and indirectly victimized at school and at home

Abstract: The results suggest that discovery of animal abuse should prompt further enquiries about other problems that a child may have. Detection of animal abuse by a child could offer an early opportunity for intervention to alleviate internalized damage or other aggressive behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 23 publications
8
77
1
Order By: Relevance
“…First, although the finding that over half of the current sample (55%) reported engaging in at least one act of animal cruelty is consistent with previous research on animal cruelty in student populations (e.g. Arluke, 2002;Baldry, 2005;Miller & Knutson, 1997;Sanders & Henry, 2015), it is possible that participants may have exaggerated or fabricated their responses. While participants were asked to complete the measures quietly and alone without discussing their responses with anyone in order to reduce the potential effects of social desirability/peer pressure it must be acknowledged that the measures were administered in social areas of the University campus (e.g.…”
Section: Limitations Of the Studysupporting
confidence: 85%
“…First, although the finding that over half of the current sample (55%) reported engaging in at least one act of animal cruelty is consistent with previous research on animal cruelty in student populations (e.g. Arluke, 2002;Baldry, 2005;Miller & Knutson, 1997;Sanders & Henry, 2015), it is possible that participants may have exaggerated or fabricated their responses. While participants were asked to complete the measures quietly and alone without discussing their responses with anyone in order to reduce the potential effects of social desirability/peer pressure it must be acknowledged that the measures were administered in social areas of the University campus (e.g.…”
Section: Limitations Of the Studysupporting
confidence: 85%
“…Bullying Empirical evidence from recent studies suggests that youth involved in bullying-both as perpetrators and victims-are more likely to abuse animals [9,26,29]. This relationship appears to be particularly true for males.…”
Section: Other Forms Of Human Violencementioning
confidence: 81%
“…The leading antecedents of children's animal cruelty have been shown to be a) being a victim of physical or sexual abuse, b) witnessing violence between one's parents, and c) witnessing parents or peers harm animals [8,9,28,45]. In addition, being bullied and/or being a bully have also been linked to children's abuse of animals [9,26,29].…”
Section: The Co-occurrence Of Animal Abuse and Inter-human Violencementioning
confidence: 96%
“…To our knowledge, only one study investigating this connection has been published. Utilizing a sample of 532 Italian children, Baldry (2005) examined how animal abuse, abuse at home, and school bullying relate. She found that boys and girls who reported participating in direct school bullying were twice as likely to have committed some form of animal abuse when compared to their non-bullying peers.…”
Section: Introductionmentioning
confidence: 99%